Las rondas para el desarrollo en la oralidad de los niños de Educación Inicial - Perdomo Anasi, Joselyn Sabrina (2022)
The present project entitled "Orality in the development of the language of children from 3 to 4 years old" whose objective was to identify the development of oral language of children through the application of the interview and the observation sheet, to develop the orality in children of initial education of the Educational Unit "Pujilí". To carry out this research, the qualitative approach itself was facilitated, which allowed obtaining real information from the direct interaction between the researcher and the object of study. The data collection instruments were the interview and the observation sheet, the same ones that allowed to evidence and know the language difficulties detected in a certain group of children, who presented conflicts in the development of oral language, which causes problems in the communicative expression and social interaction. For this reason, the objective of designing a didactic guide through the application of playful activities that allow the improvement in the orality of children is proposed based on the theme "The rounds for the development in the orality of children of Initial Education". from 3 to 4 years of the Pujilí Educational Unit. The proposal is aimed at supporting teachers in the educational process through games through the use of visual cards and traditional rounds following the pedagogical approach of Jean Piaget's structuralist game theory. Therefore, the great importance of the development of orality in children of the initial level is shown through activities that allow the strengthening of communication, interaction, expression and improvement of verbal language. The application of the didactic guide inside and outside the classroom is significant, improving the educational processes of teaching, learning and communication.